Online Marketing Strategies to Boost Sales for Pempek Dapur Bunda's Culinary Business - Hartono, Sadim (Devotion : Journal of Research and Community Service, 2025)
Conventional marketing methods are no longer sufficient to attract potential customers, as consumer behavior is increasingly reliant on digital technology. To boost pempek sales, creating a unique product has also become an essential part of the marketing strategy. This research aims to identify and analyze effective online marketing strategies that can be implemented to increase pempek sales for Pempek Dapur Bunda culinary business, focusing on leveraging digital platforms and SWOT analysis to enhance market competitiveness. This research is descriptive qualitative research utilizing a literature review method based on various sources such as articles and books. Research findings reveal nine strategic implementations: (1) Optimizing social media to build brand awareness and attract consumer attention, (2) Utilizing chatbots or customer management systems and opening all communication channels to expand target reach, (4) Learning to optimize sales through marketplaces like Facebook, TikTok, and Instagram, (5) Seeking alternative suppliers or aggregators starting through social media or customer contacts, (6) Actively promoting on social media by targeting the upper-middle class, (7) Innovating with frozen food options for raw or semi-cooked products to be distributed through souvenir shops and supermarkets, (8) Innovating take-away packaging to enhance customer satisfaction, making it a signature souvenir product from Pempek Dapur Bunda, and (9) Developing product innovations by sourcing alternative raw materials. The research concludes that integrated digital marketing strategies significantly impact consumer engagement and sales performance in traditional culinary businesses.